Identifikasi Kesulitan Belajar Akademik - Habsy, Bakhrudin All; Indah, Nur Mutiara; R, Daura Dirasyia Nadzinniya; Salsabila, Qonita (TSAQOFAH, 2024)
This article discusses the identification of academic learning difficulties that are often experienced by students. Academic learning difficulties include difficulties in reading, writing and arithmetic. The causes of academic learning difficulties can come from students' internal factors such as low cognitive abilities or external factors such as lack of support from parents or teachers. In overcoming academic learning difficulties, collaboration is needed between teachers, students and parents. Teachers must provide teaching that not only refers to the curriculum, but also looks at students' individual needs. Students must admit the difficulties they face and ask for help from teachers and parents. Parents must provide support and motivation in the learning process and teach skills needed for learning such as reading together and discussing.